2023
DOI: 10.1186/s12933-023-01780-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of the triglyceride–glucose index with coronary artery disease complexity in patients with acute coronary syndrome

Abstract: Aim The triglyceride–glucose (TyG) index has been shown to be an independent predictor for the progression and prognosis of coronary artery disease (CAD). Whether the TyG index predicts the severity of CAD in patients presenting with acute coronary syndrome (ACS) remains unknown. Methods A total of 1,007 individuals presenting with ACS undergoing coronary angiography were stratified according to the tertiles of the TyG index and The Synergy Between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Furthermore, dyslipidemia resulting from insulin resistance, characterized by increased plasma triglyceride levels, decreased levels of high-density lipoprotein (HDL), and the presence of small dense low-density lipoproteins (sdLDL) [23][24][25], also contributes to the formation of atherosclerotic plaques [8]. Consequently, the TyG index, considered as an affordable, practical, and reproducible surrogate marker of insulin resistance in comparison to the hyperinsulinemic-euglycemic clamp test and HOMA-IR [10], has shown associations with the complexity of coronary artery lesions in several observational clinical studies [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dyslipidemia resulting from insulin resistance, characterized by increased plasma triglyceride levels, decreased levels of high-density lipoprotein (HDL), and the presence of small dense low-density lipoproteins (sdLDL) [23][24][25], also contributes to the formation of atherosclerotic plaques [8]. Consequently, the TyG index, considered as an affordable, practical, and reproducible surrogate marker of insulin resistance in comparison to the hyperinsulinemic-euglycemic clamp test and HOMA-IR [10], has shown associations with the complexity of coronary artery lesions in several observational clinical studies [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…A series of recent studies have indicated that elevated TyG index is linked to a higher risk of CVD [ 7 ], CAD [ 8 ], PAD [ 9 ], and stroke [ 10 ]. Nevertheless, the relationship between TyG index and CVD mortality (CVM) and all-cause mortality (ACM) is still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Low- and middle- income countries (LMIC) has experienced a remarkable rise in the frequency of CVD and CVM in recent decades [ 12 ]. Eighty percent of CVM cases in recent years have been reported in LMIC, particularly in Middle Eastern countries [ 7 , 8 ]. Furthermore, studies have demonstrated that Iranians exhibit a greater prevalence of risk factors for CVD, central obesity [ 13 ], metabolic syndrome [ 14 ], and diabetes mellitus (DM) [ 15 ] when compared to the general population of other countries[ 16 , 17 ] that indicate impaired metabolism and hyperinsulinemia [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“… 7–9 Recently, several studies have indicated that the TyG index may be an effective indicator of the complexity and severity of CAD. 10 11 The relationship between the TyG index and the degree of coronary stenosis in individuals with acute ST segment elevation myocardial infarction (STEMI) after percutaneous coronary intervention (PCI) remains, however, poorly known. Furthermore, the studies regarding the influences of the TyG index on the poor prognosis in patients suffering from STEMI are extremely limited.…”
Section: Introductionmentioning
confidence: 99%